Design of and Experiment on Open-and-Close Seedling Pick-Up Manipulator with Four Fingers - Ni Zhang; Guozhong Zhang; Haopeng Liu; Wanru Liu; Jia Wei; Nanrui Tang (Agriculture, 2022)
With the aim to solve the problems of plug seedlings being damaged and the low success rate in the process of picking up seedlings, an open-and-close seedling picking manipulator with four fingers was designed. The clamping scheme with quadrangle inserting while clamping was designed in order to reduce the disturbance and injury of pot matrix soil. The working principle of the manipulator was expounded, and a mathematical model of the mechanism movement was established. The force transmission of the mechanism and force between finger and pot was analyzed, and the constraint condition of optimum force transmission efficiency and low damage when picking up seedlings was analyzed. Based on theoretical calculation and analysis, a set of optimal parameters and the trace curve of the finger end point were obtained. Based on the above theoretical calculation, kinematics parameters were analyzed and verified by Adams software. IF and STEP velocity functions were used to define the motion form of the driving source to simulate manipulator opening away from the seedling, straight down near the seedling, inserting into pot while clamping, and lift-off after the insertion to depth 45 mm. The simulation result proved the end point trajectory obtained by the motion simulation was basically consistent with that obtained by theoretical calculation. Velocity and acceleration curves of each mechanism component were obtained, and the result proved the velocity and acceleration of the tip of the finger changed greatly, and the inertia impact was large; the inertia force helped to clamp the pot. The manipulator was installed at the end of the transplanting platform. A plug seedling of “Zhongnong Luheng line pepper 363” was taken as the object, and the pot moisture content, seedling pick-up frequency, and finger material were used as experimental factors for the seedling pick-up test. The results showed that the above three factors had significant effects on the rate of pot damage and the rate of successful seedling pick-up. The optimum level was that when the moisture content was 45%, the frequency of picking seedlings was 20 plants·min−1, and the clamping finger material was carbon steel; the damage rate of the pot body was 1.98%, and the success rate of picking seedlings was 98%. This manipulator has the advantages of stable seedling picking and a low damage rate and can be used for transplanting plug seedlings of plants such as pepper and tomato.